Two new species of Scolopocryptops centipedes from southern Japan (Chilopoda: Scolopendromorpha: Scolopocryptopidae) - Jonishi, Taro; Nakano, Takafumi (European Journal of Taxonomy, 2023)
The blind centipede genus Scolopocryptops Newport, 1844 comprises two lineages: the “Asian/North American” group and the “Neotropical/Afrotropical” group. The former can be further split into two groups, a clade comprising Scolopocryptops elegans (Takakuwa, 1937) and Scolopocryptops curtus (Takakuwa, 1939), and a clade comprising all other “Asian/North American” species. Here, Scolopocryptops miyosii sp. nov. from Kyushu and Amami Island and Scolopocryptops brevisulcatus sp. nov. from Izena Island and Okinawa Island in southern Japan are described. The two new species have external features similar to S. elegans and S. curtus. They can be distinguished from most other “Asian/North American” Scolopocryptops by the absence of complete sulcus/sulci along the lateral margin of the cephalic plate and the presence of sternal longitudinal sulci. They can be distinguished from each other by several external features, such as the density of antennal setae and the shape of the anterior margin of the coxosternite. Phylogenetic analyses using nuclear and mitochondrial markers also support the monophyly of the four species, which form a clade sister to all other “Asian/North American” Scolopocryptops.